Analysis of The Relationship between Self-Esteem and Mortality Salience on Ethical Ideology Through Ethical Beliefs among Accounting Department - Salsabilah, Fatimah Sita; Junaidi, Junaidi; Anwar, Suhardi M.; Sahrir, Sahrir (Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to examine the relationship between self-esteem and the significance of death among accounting students towards ethical ideology through ethical beliefs. The sample consisted of 288 active accounting students from several universities in Indonesia, with structural equation modeling (SEM) used to test the research hypothesis. The research results on the mediation effect with a value of (0.288; p<0.0001) show that self-esteem through ethical beliefs as mediation significantly influences ethical ideology among accounting students, and (0.497; p<0.0001) shows that mortality salience through ethical beliefs as mediation also has a significant impact on ethical ideology among accounting students. The results of the research on the structural model directly (0.229; p<0.001, 0.986; p<0.001) show that self-esteem and mortality salience have a positive and significant effect on ethical ideology. Overall, the relationship between self-esteem and mortality salience on ethical ideology through ethical belief indicates that these two factors are interconnected and can shape the way students understand and apply ethical values.